cis-4-[18F]fluoro-L-proline Molecular Imaging Experimental Liver Fibrosis - Cao, Qi; Lu, Xin; Azad, Babak Behnam; Pomper, Martin; Smith, Mark; He, Jiang; Pi, Liya; Ren, Bin; Ying, Zhekang; Sichani, Babak Saboury; Morris, Michael; Dilsizian, Vasken (Frontiers in Molecular Biosciences, 2020)
Introduction: Early-stage liver fibrosis is potentially reversible, but difficult to diagnose. Clinical management would be enhanced by the development of a noninvasive imaging technique able to identify hepatic injury early, before end-stage fibrosis ensues. The analog of the amino acid proline, cis-4-[18F]fluoro-L-proline ([18F]fluoro-proline), which targets collagenogenesis in hepatic stellate cells (HSC), was used to detect fibrosis. Methods: Acute steatohepatitis was induced in experimental animals by liquid ethanol diet for 8 weeks, intra-gastric binge feedings every 10th day along with lipopolysaccharide (LPS) injection. The control animals received control diet for 8 weeks and an equivalent volume of saline on the same schedule as the acute steatohepatitis model. First, in vitro cellular experiments were carried out to assess [3H]proline uptake by HSC, hepatocytes and Kupffer cells derived from rats with acute steatohepatitis (n = 14) and controls (n = 14). Next, ex vivo liver experiments were done to investigate unlabeled proline-mediated collagen synthesis and its associated proline transporter expression in acute steatohepatitis (n = 5) and controls (n = 5). Last, in vivo dynamic and static [18F]fluoro-proline micro-PET/CT imaging was performed in animal models of acute steatohepatitis (n = 7) and control (n = 7) mice. Results: [3H]proline uptake was 5-fold higher in the HSCs of steatohepatitis rats than controls after incubation of up to 60 min. There was an excellent correlation between [3H]proline uptake and liver collagen expression (r-value > 0.90, p<0.05). Subsequent liver tissue studies demonstrated 2-3 fold higher proline transporter expression in acute steatohepatitis animals than in controls, and proline-related collagen synthesis was blocked by this transporter inhibitor. In vivo micro-PET/CT studies with [18F]fluoro-proline showed 2-3 fold higher uptake in the livers of acute steatohepatitis mice than in controls. There was an excellent correlation between [18F]fluoro-proline uptake and liver collagen expression in the livers of acute steatohepatitis mice (r-value = 0.97, p<0.001). Conclusions: [18F]fluoro-proline localizes in the liver and correlates with collagenogenesis in acute steatohepatitis with a signal intensity that is sufficiently high to allow imaging with micro-PET/CT. Thus, [18F]fluoro-proline could serve as a PET imaging biomarker for detecting early-stage liver fibrosis.